Analisis risiko service level, register outlet, register outlet dan retur terhadap selling out produk Heavenly Blush Yoguroto - Van Gobel, Rolly Harris; Tewu, M.L. Denny (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Every company certainly wants profits, especially when these profits are obtained from increased product sales volume. An increase in sales volume or selling out will have an impact on a company's income. Unfortunately, this increase in sales volume cannot be done alone but also requires a relationship between components such as service levels, outlet registers, and product returns. The purpose of this study is to obtain information regarding the risks of service level, register outlets, and returns on selling out of Heavenly Blush Yogurt products. The research method used is descriptive and quantitative, with data collection techniques through documentation sourced from PT Heavenly Nutrition Indonesia's internal data in the form of sales data for Yogurtland products from 2018 to 2020. The results showed that service level, register outlets, and effective outlets had a significant positive influence on the selling out of Heavenly Blush Yogurt products, while the return of goods did not have a significant effect, even though it was positive because the Sig value was > 0.05. The value of the influence provided by these various factors on product sales is 97.8%.